Nuevo gliptodonte (Mammalia, Glyptodontoidea) del Cuaternario de la provincia del Chaco (Argentina) - Zurita, Alfredo Eduardo (2002)
Chacus paskoensis is described as a new genus and species of glyptodont, based on remains from Quaternary sediments exposed at Avia Terai (Chaco province). The ornamentation of the dorsal carapace and the caudal tube allowes  to include the new taxa in the Sclerocalyptinae Sclerocalyptini; it differs from the others members  of the tribe in having  a larger size, a more globular carapace, a smaller caudal aperture in the dorsal carapace and two big depressions under the nasals. This new glyptodont was found associated with other two Sclerocalyptini, one identified as Sclerocalyptus ornatus (Owen) and the other as Sclerocalyptus sp. On this basis, a Quaternary age is inferreded for the sediements. The presence of this new genus and species permits speculation about the existence of a particular paleozoogeographic condition for the eastern Chaco region.